The Interaction Between Fatty Acid Desaturase-2 (FADS2) rs174583 Genetic Variant and Dietary Quality Indices (DASH and MDS) Constructs Different Metabolic Phenotypes Among Obese Individuals - Khodarahmi, Mahdieh; Nikniaz, Leila; Abbasalizad Farhangi, Mahdieh (Frontiers in Nutrition, 2021)
Background and aim: Genetic variation in fatty acid desaturases (FADs) has previously been linked to several diet-related diseases. We aimed to determine whether FADS2 rs1745583 variant interacts with the Dietary Approach to Stop Hypertension (DASH) score and Mediterranean dietary score (MDS) to influence cardio-metabolic risk factors among obese adults. Methods: this cross-sectional study was performed among 347 apparently healthy obese adults (aged 20–50 years). Dietary quality indicator scores (DASH and MDS) were generated using a validated 147-item Food Frequency Questionnaire (FFQ). FADS2 rs1745583 variant were genotyped by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). The gene-diet interaction was analyzed by ANCOVA multivariate interaction model. Results: Significant interaction was observed between rs174583 and adherence to DASH score in relation to serum triglyceride (TG) concentration among females (P Interaction= 0.046); CT-genotype carriers who were assigned to the second tertile of DASH compared with those in the first tertile, had the lower TG level (P <0.05). Another significant interaction was revealed between adherence to MDS score and rs174583 polymorphism on serum glucose levels (P Interaction= 0.044); the lowest mean of glucose level was observed in homozygous minor subjects (TT) in the third tertile of MDS, in comparison with other tertiles of this dietary index (P < 0.05). There was a similar significant interaction between DASH and rs174583 in relation to diastolic blood pressure (P Interaction= 0.038) among male group. Additionally, a significant positive association was found between TT genotype and odds of having high TG, either in the crude (OR, 3.21; 95% CI, 1.02-10.14) or the adjusted (OR, 3.58; 95% CI, 1.07-11.97) model taking into account different confounders. Conclusion: FADS2 rs174583 interacts with adherence to the dietary quality indicators (DASH and MDS) to affect cardio-metabolic risk factors in both obese women and men. Prospective cohort studies are needed to confirm the results of our study.